Envelope tracking power amplifiers for wireless communications - Wang, Zhancang (Artech House, 2014)
Envelope tracking technology is seen as the most promising efficiency enhancement technology for RF PA for 4G and beyond wireless communications. More and more organizations are investing and researching on this topic with huge potential academic and commercial values.